Fudge and marriage - Coco, Nancy (Coco, Nancy. Candy-coated mystery., 2025)
"June is always beautiful on Mackinac Island, which is why Allie chose this month for her wedding to police officer Rex Manning--definitely Mackinac Island's finest in more ways than one. But if her mother has her way, that's the last choice Allie will get to make. Allie's the furthest thing from a Bridezilla--but it looks like she has a Momzilla on her hands. Why else have her mother and extended family shown up a full two weeks before the nuptials to drive Allie to dizzying distraction? Honestly, a murder investigation is far less stressful--and as it happens, Allie just found Velma French dead on the ground beside the rock that killed her, with her rival Myrtle sobbing nearby. Things don't look good for Myrtle, but all may not bewhat it seems. Allie vows to solve the crime before she walks down the aisle. But a killer has other ideas--and they seem to be focused on Allie herself..."--